2020
DOI: 10.1055/s-0040-1718737
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Glycoprotein VI in Mouse and Human Thrombus Progression and Stability

Abstract: Letter to the Editor This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These data are in agreement with our flow cytometry results, showing no binding to GPVI on the platelet surface in these animals. The previous studies revealed discrepancies between the mouse and human GPVI affinity to specific ligands and discussed possible differences with regard to the relevance of this receptor in thrombosis [ 41 ], thus, underscoring the need to utilize humanized animal models. Indeed, our newly generated mouse line allowed us to faithfully reproduce the results obtained with human platelets, thereby excluding the possible overlapping effects of FcγRIIa, which is present in human but not mouse platelets and signals through a similar pathway as GPVI.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with our flow cytometry results, showing no binding to GPVI on the platelet surface in these animals. The previous studies revealed discrepancies between the mouse and human GPVI affinity to specific ligands and discussed possible differences with regard to the relevance of this receptor in thrombosis [ 41 ], thus, underscoring the need to utilize humanized animal models. Indeed, our newly generated mouse line allowed us to faithfully reproduce the results obtained with human platelets, thereby excluding the possible overlapping effects of FcγRIIa, which is present in human but not mouse platelets and signals through a similar pathway as GPVI.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that GPVI mediates a signal following platelet adhesion to fibrinogen which is distinct from αIIb|33 outside-in signaling and that the signaling measured upon platelet adhesion to fibrinogen cannot be exclusively related to outside-in signaling as reported so far. Importantly, only human but not murine GPVI is a functional receptor for fibrinogen, 78 which explains a long unanswered question why resting mouse platelets deposited on immobilized fibrinogen do not spread. This was notably demonstrated by the observation that expression of human GPVI in mouse platelets led to a nice spreading on fibrinogen as human platelets do.…”
Section: The Activation State Of Integrins and Integrin Signalingmentioning
confidence: 99%
“…A comparison of the roles of human and mouse GPVI in platelet aggregation and thrombus stability indicated that especially the blockage of human platelet GPVI led to disaggregation [ 42 ]. In mice, most markedly a deficiency in integrin β3 led to a transient collagen-mediated platelet aggregation and an unstable thrombus formation [ 43 ].…”
Section: Collagen Gpvi Receptor Stimulationmentioning
confidence: 99%